2013
DOI: 10.1371/journal.pone.0065372
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Skeletal Muscle Mass Changes in Chronic Kidney Disease Stage 4 and 5 Patients: An Observational Study

Abstract: Cross-sectional studies in dialysis demonstrate muscle wasting associated with loss of function, increased morbidity and mortality. The relative drivers are poorly understood. There is a paucity of data regarding interval change in muscle in pre-dialysis and dialysis-dependant patients. This study aimed to examine muscle and fat mass change and elucidate associations with muscle wasting in advanced CKD.134 patients were studied (60 HD, 28 PD, 46 CKD 4–5) and followed up for two years. Groups were similar in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 38 publications
3
59
0
1
Order By: Relevance
“…The differences with the results presented here could be explained by the relatively small size of our study in comparison and the chance of it being underpowered. John et al used CT measurements of muscle cross sectional area around HD initiation which also showed similar trends as this data [26]. Interestingly, this study showed that pre-dialysis patients exhibited an even greater rate of muscle loss and that dialysis initiation actually reduced the rate of muscle loss.…”
Section: Discussionsupporting
confidence: 73%
“…The differences with the results presented here could be explained by the relatively small size of our study in comparison and the chance of it being underpowered. John et al used CT measurements of muscle cross sectional area around HD initiation which also showed similar trends as this data [26]. Interestingly, this study showed that pre-dialysis patients exhibited an even greater rate of muscle loss and that dialysis initiation actually reduced the rate of muscle loss.…”
Section: Discussionsupporting
confidence: 73%
“…The Chronic Renal Insufficiency Cohort (CRIC) study revealed that the prevalence of frailty and pre-frailty in stage G2–4 CKD was 7% and 43%, respectively, and that lower kidney function was associated with frailty [32]. Another study showed that muscle mass, evaluated by multi-slice CT, longitudinally declined with time especially in nondialysis-dependent patients and incident hemodialysis patients [33]. …”
Section: Frailty and Muscle Wasting In Chronic Kidney Diseasementioning
confidence: 99%
“…5(3), 1224-1229 1225 Several decades of research efforts devoted to studying the patterns of chronic kidney disease-end stage renal disease (CKD-ESRD) progression as well as the impact of acute kidney injury (AKI) on this continuum of CKD-ESRD evolution but the full understanding of the process (es) of CKD-ESRD progression remains elusive 2 .Significant muscle weakness and associated atrophy is seen in both dialysis patients and in patients with chronic kidney disease (CKD) stages 3-4. This is associated with increased morbidity and mortality 3, 4 .…”
Section: Issn: 2320-5407mentioning
confidence: 99%